Association Between Circulating Retinol-Binding Protein 4 and Adverse Cardiovascular Events in Stable Coronary Artery Disease - Qian, Ke; Yan, Xin; Xu, Cheng; Fang, Yijia; Ma, Moshuang (Frontiers in Cardiovascular Medicine, 2022)
Background: The predictive role of retinol-binding protein 4 (RBP4) in the adverse prognosis of patients with stable coronary artery disease (CAD) has not been well-defined. We thus conducted this cohort study to investigate the association between circulating RBP4 level and major adverse cardiovascular events (MACEs) in Chinese patients with stable CAD. Methods: Patients with stable CAD and serum RBP4 concentration measurement at admission between July 2012 and January 2015 were included. The primary outcome in this study was incident MACEs, which included acute coronary syndrome, heart failure, stroke, peripheral vascular disease, and cardiovascular death. Cox proportional hazards regression was adopted to investigate the association between RBP4 and the incidence of MACEs. Results: A total of 840 patients with stable CAD were analyzed. The mean age of patients was 61.2±15.9 years old and 56.1% of them were men. After a median follow-up of 2.3 years, 129 MACEs were observed. Compared to participants exposed to the first quartile of serum RBP4 level, those in the second, the third, and the fourth quartiles had an associated hazard ratios (HRs) of 2.38 (95% confidence interval (CI): 1.33–4.26), 2.35 (95% CI: 1.31–4.21), and 2.27 (95% CI: 1.28–4.04) after adjusted for confounders, respectively. Every 5 µg/mL increment in serum RBP4 concentration was associated with an adjusted HR of 1.13 (95% CI: 1.05–1.22) for MACEs occurrence. Subgroup analyses suggested no significant modifying effects of baseline characteristics for the association between RBP4 and MACEs in patients with stable CAD. Conclusion: Our finding suggested that the higher circulating RBP4 level were significantly associated with increased risk of MACEs in patients with stable CAD.